Articulação Modular para Braços Robóticos - Marco António Mendonça Rocha (2021)
The variety of processes to be automated in industry represents a wide range of options. So, robotic arms must be as flexible as possible in terms of their configuration. Consequently, the modular joints allow to easily configure a robotic arm with the desired characteristics for a given process. That is, a robotic arm can be built with as many joints as the number of degrees of freedom wanted, and physical connections can be placed between the joints in order to constitute the manipulator. Consequently, this work consists on the development of a modular joint for robotic arms with the following characteristics: compact, low cost, easily reconfigurable, with low backlash and with speed and position control incorporated. Thus, after a study of the different types of gearboxes, we opted for the use of a compound planetary gearbox, as it allows to obtain a high reduction ratio without dramatically increasing backlash. Additionally, in relation to the motor, it was used a brushed DC, which contributes to the low final cost of the joint. An ATmega328P microcontroller is incorporated into this joint, where the joint position and speed control algorithms are executed. In order to make it possible to carry out the control safely, this joint has the following sensors: voltage, current, temperature, absolute magnetic encoder, and Hall sensor for "Home Position". This joint also has communication to receive external commands for position and speed control.